2023
DOI: 10.3390/brainsci13020266
|View full text |Cite
|
Sign up to set email alerts
|

Ranitidine Alleviates Anxiety-like Behaviors and Improves the Density of Pyramidal Neurons upon Deactivation of Microglia in the CA3 Region of the Hippocampus in a Cysteamine HCl-Induced Mouse Model of Gastrointestinal Disorder

Abstract: Elevated levels of histamine cause over-secretion of gastric hydrochloric acid (HCl), leading to gastrointestinal (GI) disorders and anxiety. Ranitidine is an antihistamine drug widely used in the management of GI disorders, as it works by blocking the histamine−2 receptors in parietal cells, thereby reducing the production of HCl in the stomach. While some reports indicate the neuroprotective effects of ranitidine, its role against GI disorder-related anxiety remains unclear. Therefore, we investigated the ef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…Moreover, somatostatin pretreatment in experimental rat models mimicking PD has been reported to show resistance against lipopolysaccharide-induced neurodegeneration in the SN by preventing the activation of microglia and the accumulation of reactive oxygen species [33]. In a recent finding, we demonstrated that the administration of Cys-HCl induced an anxiety-like phenotype in the experimental animals in correlation with the reduced neuronal density and increased activation of microglia cells in the hippocampus [8,18]. While, in the intact brain, somatostatin plays a key role in olfaction and mood, affective disorders and olfactory dysfunctions have been established as non-motor clinical symptoms of many neurodegenerative disorders, including PD [30,34,35].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Moreover, somatostatin pretreatment in experimental rat models mimicking PD has been reported to show resistance against lipopolysaccharide-induced neurodegeneration in the SN by preventing the activation of microglia and the accumulation of reactive oxygen species [33]. In a recent finding, we demonstrated that the administration of Cys-HCl induced an anxiety-like phenotype in the experimental animals in correlation with the reduced neuronal density and increased activation of microglia cells in the hippocampus [8,18]. While, in the intact brain, somatostatin plays a key role in olfaction and mood, affective disorders and olfactory dysfunctions have been established as non-motor clinical symptoms of many neurodegenerative disorders, including PD [30,34,35].…”
Section: Discussionmentioning
confidence: 78%
“…PD has been linked to the inhibition of mitochondrial monoamine oxidase, which might be highly relevant in the context of the reduced levels of dopaminergic neurons in the brains of Cys-HCl-treated mice [44,45]. The Cys-HCl administration-induced reduction in antioxidants in experimental brains has become increasingly evident [18]. The anticancer effect of Cys-HCl has been reported to be associated with mitochondrial degeneration linked to the accumulation of iron, and this event activates peroxidase-positive autophagosomes, ultimately leading to cell death [46,47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, pretreatment of somatostatin in experimental rat models mimicking PD has been reported to show resistance against lipopolysaccharide-induced neurodegeneration in SN by preventing the activation of microglia and accumulation of reactive oxygen species [26]. In a recent findings, we have demonstrated that administration of cysteamine HCl induced anxiety-like phenotype in the experimental animals in correlation with reduced neuronal density and increased activation of microglia cells in the hippocampus [8,27]. While in the intact brain, somatostatin plays a key role in olfaction and mood, affective disorders and olfactory dysfunctions have been established as nonmotor clinical symptoms of many neurodegenerative disorders including PD [23,28,29].…”
Section: Discussionmentioning
confidence: 91%
“…PD has been linked to the inhibition of mitochondrial monoamine oxidase, which might be highly relevant in the context of reduced levels of dopaminergic neurons in the brain of cysteamine HCl-treated mice [38,39]. Meantime, cysteamine administrationinduced reduction of antioxidants in the experimental brains has become incorrectly evident [27]. The anticancer effect of cysteamine has been reported to be associated with mitochondrial degeneration linked to the accumulation of iron and this event activates peroxidase-positive autophagosomes, ultimately leading to cell death [40,41].…”
Section: Discussionmentioning
confidence: 99%